If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5s + 4s + 15 = -56 Reorder the terms: 15 + 5s + 4s = -56 Combine like terms: 5s + 4s = 9s 15 + 9s = -56 Solving 15 + 9s = -56 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 9s = -56 + -15 Combine like terms: 15 + -15 = 0 0 + 9s = -56 + -15 9s = -56 + -15 Combine like terms: -56 + -15 = -71 9s = -71 Divide each side by '9'. s = -7.888888889 Simplifying s = -7.888888889
| 3x^2-16x-35=03 | | 5(3x-2)=2(3x+5) | | 9y+3x=18 | | 48=-2-12x | | 17=5(-7-4k)+4(1+8k) | | -4x-bx= | | -339=8(4+7v)-3v | | -117=-9h | | 0.3j+1.8=0.4(j+5)-0.2 | | 3.6r=43.2 | | 33x-10=7x+3 | | 17=5(-7-4k)+4(1+8x) | | x^2+y=37 | | 2-3x=8x-4 | | 5x-25=2x | | 3x+19=39 | | 8(-6f-4)+9= | | 7k+17=3k-3 | | r^4+4r^3-21r^2= | | 3[2a+7]+6=3a+18 | | 3n=7.7 | | -0.5(-10+12n)=1/3(-15n-15) | | -2(1-3v)=26 | | (x/9)=(x/7)+(1/9) | | 4+4x=64 | | 10x^2-2y=0 | | x^2(2x^2-5x+3)=0 | | 4+2(z-2)=-7z+7 | | lnx+ln(x-6)=3 | | 5j=-32+15 | | 7d+2d-4d-5-3d=0 | | 20+4x=6x-6(1-4x) |